Significant friction reduction of high-intensity pulsed ion beam irradiated WC-Ni against graphite under water lubrication - Gaolong Zhang; Yuechang Wang; Ying Liu; Xiangfeng Liu; Yuming Wang (Friction)
Abstract Two types of commercial WC-Ni samples were irradiated with the High-intensity pulsed ion beam (HIPIB). Both the surface characteristics and tribo-characteristics of the non-irradiated and irradiated WC-Ni samples, sliding against graphite under water lubrication, were compared. Quite low steady friction coefficients (approximately of 0.02) of the irradiated WC-Ni were observed. The surface topographies and components were investigated. The quite low friction of the irradiated WC-Ni samples was ascribed to the higher fluid retention capability of the latter and the tribofilm formed during sliding.